Survei Ketersediaan Sarana Prasarana Sekolah Berdasarkan Standar Permendikbudristek - Tuanany, Nursyahar Jihan (Universitas Negeri Malang, 2024)
Abstract School facilities and infrastructure must meet minimum standards, which in this case can be seen from PERMENDIKNAS No.24 of 2007 article 1. To improve the quality of education, the Indonesian government re-issued the Minister of Education and Culture Regulation No. 22 of 2023 concerning standards for facilities and infrastructure in early childhood education, primary education, and secondary education. The existence of limited infrastructure facilities requires an effort to optimize infrastructure facilities in each school. The quantitative descriptive research method was used by the researcher to describe the availability of school facilities and infrastructure as well as the strategies of school leaders in optimizing facilities and infrastructure. The sources of this research included the principal and several students who were taken using random sampling. The results of the questionnaire calculation obtained an average percentage of 53% for the availability and quality of infrastructure facilities in the first school, while the second school obtained a result of 56%. It can be concluded that the availability and quality of infrastructure facilities in both schools are in the sufficient category. The limited area of the location hinders the development to complete the school infrastructure facilities. The success of school leaders' strategies in optimizing infrastructure facilities can be seen in good procurement, utilization, and inventory as well as increased creativity and innovation of teachers and students in utilizing the available facilities. Abstrak Sarana dan prasarana sekolah harus memenuhi standar minimum yang dalam hal ini dapat dilihat dari PERMENDIKNAS No.24 Tahun 2007 pasal 1. Dalam upaya meningkatkan kualitas pendidikan, pemerintah Indonesia kembali menerbitkan Peraturan Menteri Dikbudristek No 22 Tahun 2023 tentang standar sarana dan prasarana pada pendidikan anak usia dini, jenjang pendidikan dasar dan jenjang pendidikan menengah. Adanya keterbatasan sarana prasarana mengharuskan adanya suatu upaya dalam mengoptimalkan sarana prasarana pada setiap sekolah. Metode penelitian deskriptif kuantitatif digunakan oleh peneliti untuk mendeskripsikan ketersediaan sarana prasarana sekolah serta strategi pemimpin sekolah dalam optimalisasi sarana dan prasarana. Narasumber penelitian ini diantaranya kepala sekolah dan beberapa siswa yang diambil menggunakan random sampling. Hasil perhitungan angket diperoleh persentase rata-rata sebesar 53% untuk ketersediaan dan kualitas sarana prasarana di sekolah pertama, sedangkan dari sekolah kedua diperoleh hasil sebesar 56%. Dapat disimpulkan bahwa ketersediaan dan kualitas sarana prasarana di kedua sekolah dalam kategori cukup. Terbatasnya luas lokasi menghambat pembangunan untuk melengkapkan sarana prasarana sekolah. Keberhasilan strategi para pemimpin sekolah dalam optimalisasi sarana prasarana terlihat dari pengadaan, pemanfaatan, dan inventarisasi yang baik serta peningkatan kreativitas dan inovasi guru dan siswa dalam memanfaatkan fasilitas yang tersedia.